(untitled) - Bearden, William O. (Boston, MA., 2004)
"Marketing: Principles and Perspectives, 5e" is a cutting edge text. In the first four editions, we demonstrated this leading coverage with our strong integration of Integrated Marketing Communication, cross-functional teams, and integration of the Internet throughout. The authors not only talk about what marketing is, but prepare students to be marketers by involving them in interactive exercises which strengthen decision making skills. The perspectives approach is present in the fifth edition; however, the over-riding theme concentrates on building customer equity.
Keywords: Marketing; United states